Կայսերական Գերմանիայի դիրքորոշումը հայ գաղթականության նկատմամբ 1916-1917 թթ. - Գևորգ Մելքոնյան (ՀՀ ԳԱԱ հրատ.)
This article discusses the position of Germany toward the Armenian refugees exiled to the dessert regions of the Ottoman Empire during World War I.
Keywords: Armenian Question; Social Sciences; World War I